Módulo agente gerenciável de replicação de arquivos estáticos para aplicações PHP que utilizam redes de distribuição de conteúdo - Carnevalli, José Luís Tadeu Lins (2013)
This paper presents a study on strategies for distributing requests among web servers through replication of static files in geographically dispersed servers. Analyzes the models implemented by Akamai and Google Global Cache networks, and the methods of acquisition Origin-pull and Push. Finally, adopts the Push acquisition method and develops a replication agent easily integrated to a PHP application that allows managing files stored remotely on a content distribution network. The Development methodology uses an adapted version of the Unified Process, UML diagrams for creating models and object-oriented coding.